2012
DOI: 10.1016/j.medine.2012.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Intubated patients developing tracheobronchitis or pneumonia have distinctive complement system gene expression signatures in the pre-infection period: A pilot study

Abstract: Introduction: It remains unknown why some intubated patients remain infection-free while others develop tracheobronchitis (VAT) or pneumonia (VAP).Objective: To identify and compare VAP/VAT gene expression ''signatures'' using genome-wide oligonucleotide microarrays. Material and methods: A prospective translational study of gene expression profiles of VAP and VAT groups was carried out, establishing comparisons in both pre-infection and infection phases. Pathway and functional analyses were performed with Ing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
(9 reference statements)
1
10
0
1
Order By: Relevance
“…Observational studies of ventilator‐associated pneumonia (VAP) and ventilator‐associated tracheobronchitis (VAT) have revealed subsets of patients who progress directly from asymptomatic airway colonization to either type of infection as well as those with tracheobronchitis who progress to pneumonia . Pilot studies of VAP and VAT patients have found distinctive complement system gene expression signatures in the preinfection period, suggesting that these diseases have distinct pathways of pathogenesis . The unique signatures of pneumonia and tracheobronchitis in our study lend support to a similar model of divergent pathogenesis among lung transplant recipients who are not mechanically ventilated (Figure ).…”
Section: Discussionsupporting
confidence: 74%
“…Observational studies of ventilator‐associated pneumonia (VAP) and ventilator‐associated tracheobronchitis (VAT) have revealed subsets of patients who progress directly from asymptomatic airway colonization to either type of infection as well as those with tracheobronchitis who progress to pneumonia . Pilot studies of VAP and VAT patients have found distinctive complement system gene expression signatures in the preinfection period, suggesting that these diseases have distinct pathways of pathogenesis . The unique signatures of pneumonia and tracheobronchitis in our study lend support to a similar model of divergent pathogenesis among lung transplant recipients who are not mechanically ventilated (Figure ).…”
Section: Discussionsupporting
confidence: 74%
“…Immune factors are likely to play a role in determining whether a patient with VAT goes on to develop VAP. In a study of mechanically ventilated patients with VAP, patients showed a relative depression of genes involved in calcium signaling pathways, the complement system and cyclic adenosine monophosphate (Martin-Loeches I, 2012). Patients with VAP exhibit increased inflammation and worse outcomes than those with VAT, and this may be related to an immunosuppressed state (Martin-Loeches I, 2015).…”
Section: Bodymentioning
confidence: 99%
“…It might be that specific immunological mechanisms of importance are not affected in all immunocompromised patients [1]. One of the few studies on this topic suggests that complement activation is an important mechanism in the containment of VAT and this part of the innate response is little influenced by most of the studied immunosuppressed states [20]. However, there is a strong need for more evidence on the immunological and biochemical mechanisms that determine the progression towards pneumonia.…”
Section: Cough Mucociliary Clearancementioning
confidence: 99%